Minimally Invasive Punch Biopsy for Malignant Brain Tumor - de Carvalho, Jamerson Ademir Cantarelli; dos Santos, Letícia Adrielle; de Oliveira, Arthur Maynart Pereira; Abreu, Gabriel Lucas Souza; Duarte, Ivison Xavier; Vieira, Isaac Lohan Matos; Santos, Bruno Fernandes de Oliveira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
To describe an innovative minimally invasive technique for brain lesion biopsy with low cost, high precision, and reduced surgical risk in addition to providing sufficient material for pathological analysis.This is a consecutive series of cases of patients with intracranial expansive lesions with low resection possibility and high surgical risk. They were admitted to the Sergipe Emergency Hospital from March 2020 to November 2020. The approach point was determined using the NeuroKeypoint app.The same procedure was performed on five patients with sedation and local anesthesia. The small treatment required reduced surgical time. All five patients had a diagnosis after collecting performed with the device and did not experience any complications associated with the method. All patients were discharged the following day, maintaining their preoperative neurological condition. Of the five patients who underwent surgery, all had confirmatory results of malignant brain tumors, with 100% accuracy, confirming the diagnosis and enabling oncological therapeutic follow-up. During the 30-day follow-up, three patients received adjuvant therapy, while two died from systemic oncological complications.The presented method is feasible, safe, and has acceptable diagnostic accuracy, offering an alternative for diagnosing histological malignant brain tumors through minimally invasive biopsy.
Keywords: brain neoplasms; biopsy; low-cost technology; culturally appropriate technology